Primordialisme dalam problematika childfree (Studi Kasus Etnografi Pada Masyarakat Kelurahan Mlajah, Kabupaten Bangkalan) - Afrisyah, Misbahul; Kurniawa, Bima (Journal of Contemporary Issues in Primary Education, 2024)
The Madurese people can be said to be an ethnic group that upholds existing cultural values.    Just like when Kyai's descendants are required to marry Kyai's descendants as well. This research focuses on the phenomenon where the condition of the Madura community mentioned has a rejection of new ideas such as Childfree.  In the initial observation of the researcher at the research location, namely in Mlajah Village, Bangkalan Regency, there was a condition where the environment had been transformed like the life of the metropolitan community and it was found that there were people there who had an understanding of the concept of Childfree. The theory used in this study is Albert Bandura's Social Cognitive Theory. This type of research is qualitative with an ethnographic case study approach. The paradigm used in this study uses the post-positivism paradigm. The technique for determining informants in this study uses a purposive sampling technique, where the researcher determines the conditions and criteria for a person to become a research informant. The data collection techniques in this study include observation, interviews, documentation and literature studies. The data validity technique in this study uses Miles and Huberman's interactive model, which includes, data collection, data reduction, data presentation and conclusion drawn.